Partisipasi Masyarakat dalam Program Pemberdayaan Desa Wisata Pandansari di Kecamatan Warungasem, Kabupaten Batang - Muhammad Imam Baihaqi; Amin Yusuf (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
The phenomenon of community participation in rural tourism empowerment programs in Indonesia shows disparities, where participation is often limited to certain groups. Meanwhile, vulnerable groups such as farmers and women are often less involved, which of course hinders the sustainability of village development. This research aims to analyze the level and form of community participation in the Pandansari Tourism Village Empowerment Program, as well as to identify supporting and hindering factors. Using a qualitative approach with a case study design, data was then obtained thru in-depth interviews, participant observation, and document analysis. The research findings revealed that participation was strongest during the implementation phase but weak during the planning and evaluation phases, with supporting factors such as local leadership and institutional support. However, barriers included limited access to information and social capital. The novelty of the research lies in the integration of Arnstein's Ladder framework with the Sustainable Livelihood Framework to examine the dynamics of participation in the context of coastal-agrarian tourist villages and provide in-depth insights into power relations and local livelihood strategies.